Pharmacological inhibition of the PI3K/PTEN/Akt and mTOR signalling pathways limits follicle activation induced by ovarian cryopreservation and in vitro culture - Carmen Terren; Michelle Nisolle; Carine Munaut (BMC, 2021)
Abstract Background Cryopreservation and transplantation of ovarian tissue (OTCTP) represent a promising fertility preservation technique for prepubertal patients or for patients requiring urgent oncological management. However, a major obstacle of this technique is follicle loss due to, among others, accelerated recruitment of primordial follicles during the transplantation process, leading to follicular reserve loss in the graft and thereby potentially reducing its lifespan. This study aimed to assess how cryopreservation itself impacts follicle activation. Results Western blot analysis of the PI3K/PTEN/Akt and mTOR signalling pathways showed that they were activated in mature or juvenile slow-frozen murine ovaries compared to control fresh ovaries. The use of pharmacological inhibitors of follicle signalling pathways during the cryopreservation process decreased cryopreservation-induced follicle recruitment. The second aim of this study was to use in vitro organotypic culture of cryopreserved ovaries and to test pharmacological inhibitors of the PI3K/PTEN/Akt and mTOR pathways. In vitro organotypic culture-induced activation of the PI3K/PTEN/Akt pathway is counteracted by cryopreservation with rapamycin and in vitro culture in the presence of LY294002. These results were confirmed by follicle density quantifications. Indeed, follicle development is affected by in vitro organotypic culture, and PI3K/PTEN/Akt and mTOR pharmacological inhibitors preserve primordial follicle reserve. Conclusions Our findings support the hypothesis that inhibitors of mTOR and PI3K might be an attractive tool to delay primordial follicle activation induced by cryopreservation and culture, thus preserving the ovarian reserve while retaining follicles in a functionally integrated state.